The Halliwick Concept: Toward A Collaborative Aquatic Approach - Kokaridas, Dimitrios; Lambeck, Johan (Inquiries in Physical Education and Sport, 2015)
The purpose of this article is to present a contemporary picture of the Halliwick Concept– from Water Specific Therapy (WST) to the Ten-Point-Program (TPP) - and to identify potential areas of further development by proposing a collaborative approach using the Halliwick Concept. The authors acknowledge differences in philosophies of both WST and TPP, and propose that the Halliwick Concept can serve as a key organizing framework within any aquatic program that, depending on its therapeutic, educational or recreational goals, can impact the entire scope of adapted water activities. The article discusses common Halliwick Concept principles through which aquatic personnel could collaborate in the future using a common philosophy and terminology to achieve mutual goals.